Pengaruh Krisis terhadap Nilai Ekspor Kakao Indonesia di Pasar Internasional - Achmad Subchiandi Maulana; Melkisedik Bukifan; Yohanes Pebrian Vianney Mambur; Boanerges Putra Sipayung (AGRIMOR, 2023)
Cocoa is one of the important commodities in the plantation industry which is marketed in international trade, one form of international trade is export. Indonesia's cocoa export destination countries are Malaysia, America, India, China, the Netherlands, Germany, and Australia. Export activities are usually influenced by the country's economic conditions, so that the global crises in 1998, 2008, 2011, and 2020 are thought to have affected Indonesia's cocoa exports. This study uses a gravity model approach to examine the impact of the crisis on cocoa export value. The variables used in this study are the value of Indonesia's cocoa exports (EXVAL) and GDP per capita (GDPCAP), the exchange rate of the destination country's currency against the US dollar (ER), and economic distance as the dependent variable. (ECODIST) and crisis (CRISIS) as the independent variable. The emergency variable is used as a dummy variable. The results of the analysis of the gravity regression model show that all independent variables are significantly based on the t-test with the coefficient values of GDPCAP, ER, ECODIST, and CRISIS of 2.10, 2.28, –0.71, and 0.28 with an R2 value of 82%. . The crisis variable has a positive effect on the value of Indonesia's cocoa exports, so that the crisis does not weaken the development of Indonesia's cocoa exports.